Evaluasi Terhadap Asumsi Teoritis Individualisme dan Kolektivisme: Sebuah Studi Meta Analisis - Susana, Tjipto (Faculty of Psychology, Universitas Gadjah Mada, 2005)
Since Hofstede (1980) published hisÂ research about individualismâ€collectivismÂ differences among countries, interest in crosscultural study increased dramatically. HoweverÂ not all studies support each other. So the purposeÂ of this study is to evaluate primary studies thatÂ studied individualismâ€collctivism differences.Â Articles selected from electronic databaseÂ (e.g. Proquest, EBSCO, and ERIC) forpublication. Forty nine studies were found, butÂ only 15 studies that were relevant. After finalÂ evaluation, only 3 studies with 7 data pointsÂ that actually could be analized.Â This study found that there are differencesÂ between individualist and collectivist countriesin horizontal collectivism. People in collectivistÂ countries are more collectivist than people inÂ individualist countries. In vertical individualism,Â horizontal individualism, and verticalÂ collectivism dimension, homogeneity coefficientÂ (Q) shows that sample drawn from the sameÂ source differ systematically. However we cannot do moderator analysis because of number ofÂ studies are limited. Thus, this study can notÂ explain moderator variables that influence effectcÂ size variation.